Science Learning Videos Based on Contextual Approaches for Grade V Elementary Schools - Wedaswari, Ni Made Natalia; Tegeh, I Made (International Journal of Elementary Education, 2023)
This development research is motivated by the use of learning media in elementary schools that are not optimal, and teachers still use conventional media, therefore developing learning videos based on a contextual approach to science learning for fifth-grade students. This study aims to develop contextual approach-based video scribe learning videos. This development research used the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). This type of research is research and development. The subjects of this study were three experts, three students, and six students. Data collection methods are observation, interviews, document studies, tests, and questionnaires. The instrument is a rating scale using data analysis techniques, namely descriptive qualitative, quantitative, and inferential statistics. The results of this study are to produce a contextual approach-based video scribe learning video design to increase student interest in learning and to improve the learning outcomes of fifth-grade elementary school students. The average score of media validity is 95%, the average score of content validity is 92%, and the average score of design validity is 95% with a very good predicate, and video scribe learning videos based on a contextual approach is effective in improving the ability of learning outcomes. So, developing a learning video based on a contextual approach to science learning for grade V elementary school students is feasible and effective for improving the learning outcomes of grade V students on water cycle material for fifth-grade elementary school students.